Analysis of Nutritional Status among Adolescent Girls - Surani Surani; Vivi Silawati; Rukmaini Rukmaini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nutrition is a crucial component and plays a central role in achieving 13 of the 17 Sustainable Development Goals (SDGs). Through improving nutrition, many other goals can be achieved, leading to the betterment of a nation. The general objective of this study is to determine the influence of nutritional status and its impact on the health of adolescent girls in the Tapos District, Depok City. The type of research used is quantitative, where the results of calculations or measurements are in numerical form. This study employed a cross-sectional approach. The population in this study were all female adolescents in grades X, XI, XII at SMK Mutiara and SMKN 1 Tapos Depok, which were 254 people. The sampling technique used in this research is total sampling. The sample used in this study was the total population, namely female adolescents in grades X, XI, XII of SMK Mutiara and SMKN 1 Tapos Depok. The research data collection procedure begins with the researcher taking several steps, namely taking care of the research permit letter at the National University, collecting data, both primary data and secondary data in the Tapos Depok District Area, requesting research permission from the Principal of the Tapos Depok District Area, explaining to potential respondents about the research and signing informed consent if they are willing to be respondents, explaining how to fill out the questionnaire to respondents, respondents fill out all the questions in the questionnaire that have been given by the researcher, and if they have finished the questionnaire is submitted to the researcher. After the data is collected, data collection is carried out, then data processing and data analysis are carried out, and the research results report is prepared. Univariate analysis is the analysis of each variable from the research results to create a frequency distribution and percentage of each variable. Bivariate analysis is an analysis carried out on two variables that are suspected to be related or correlated, namely using chi square. The multivariate data analysis technique used in this study is multiple logistic regression analysis.. Body image on nutritional status in female adolescents obtained a p value of 0.001. Eating patterns on nutritional status in female adolescents obtained a p value of 0.001. Nutrition knowledge on nutritional status in female adolescents obtained a p value of 0.001. Snacking behavior on nutritional status in female adolescents obtained a p value of 0.001. Parental income on nutritional status in female adolescents obtained a p value of 0.001. Health worker support on nutritional status in female adolescents obtained a p value of 0.001. Parental support on nutritional status in female adolescents obtained a p value of 0.001. Nutritional status on physical health in female adolescents obtained a p value of 0.001. Nutritional status on mental health in female adolescents obtained a p value of 0.001. Based on the 10 variables, the most significantly correlated variable is body weight, based on the chi-square statistical test, which showed a p-value of 0.001.